2015
DOI: 10.1002/hep.27587
|View full text |Cite
|
Sign up to set email alerts
|

Variations in serum sphingolipid levels associate with liver fibrosis progression and poor treatment outcome in hepatitis C virus but not hepatitis B virus infection

Abstract: Ablation of very-long-chain ceramides (Cers) with consecutive elevations in sphinganine levels has been shown to cause a severe hepatopathy in a knockout mouse model. We have recently shown that serum sphingolipids (SLs) are deregulated in patients with chronic liver disease. However, their role as possible biomarkers in liver fibrosis remains to date unexplored. We assessed, using liquid chromatography/tandem mass spectrometry, serum concentrations of various SL metabolites in 406 patients with chronic viral … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
65
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 45 publications
(74 citation statements)
references
References 49 publications
8
65
0
1
Order By: Relevance
“…Disruptions of SL metabolism were described in hepatitis B (HBV) and C (HCV) infection, including increased expression of genes that is involved in the metabolism and transport of SLs, phospholipids, and fatty acids (33, 35, 45-47, 165, 169, 180, 184). C18DHC, C24Cer, SPH, and sphinganine were significantly linked with the level of liver fibrosis (62,44,66). However, a high correlation between variations in serum SL levels and responsiveness to antiviral therapy was shown.…”
Section: Sl Pathways In Diabetes Nafld and Nashmentioning
confidence: 89%
See 4 more Smart Citations
“…Disruptions of SL metabolism were described in hepatitis B (HBV) and C (HCV) infection, including increased expression of genes that is involved in the metabolism and transport of SLs, phospholipids, and fatty acids (33, 35, 45-47, 165, 169, 180, 184). C18DHC, C24Cer, SPH, and sphinganine were significantly linked with the level of liver fibrosis (62,44,66). However, a high correlation between variations in serum SL levels and responsiveness to antiviral therapy was shown.…”
Section: Sl Pathways In Diabetes Nafld and Nashmentioning
confidence: 89%
“…Analysis of lipids from the hepatic portal system at the time of surgery revealed that PG and PE classes were increased in NASH subjects; moreover, few alterations were noted in adipose tissue lipid efflux (9,10,39). Serum SLs are dysregulated in patients with several chronic liver diseases, suggesting their role in liver damage (44,62,66). Disruptions of SL metabolism were described in hepatitis B (HBV) and C (HCV) infection, including increased expression of genes that is involved in the metabolism and transport of SLs, phospholipids, and fatty acids (33, 35, 45-47, 165, 169, 180, 184).…”
Section: Sl Pathways In Diabetes Nafld and Nashmentioning
confidence: 99%
See 3 more Smart Citations